The Impact of Shift Work Systems and Workload on Employee Productivity: Pengaruh Sistem Kerja Shift dan Beban Kerja Terhadap Produktivitas Karyawan - Sulistiana, Chindy; Purwanto, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The purpose of this study was to analyze the effect of shift work system and workload on employee productivity in the production department of PT Setia Raya Mandiri, Serang Regency branch, and to provide recommendations that can help companies improve work effectiveness and reduce the level of rejects. This type of research is related to descriptive quantitative research. The subjects or participants in this study were all employees of PT Setia Raya Mandiri, Production Department, Serang Regency Branch, totaling 41 people. Primary data were collected through a closed questionnaire method distributed to employees online. Data obtained from the results of distributing the questionnaire were analyzed quantitatively using descriptive statistical analysis and analysis of relationships between variables. Furthermore, relationship analysis was used to determine the relationship or influence between the variables studied, with the help of SPSS statistical software version 26.0. Validity testing was carried out by comparing the calculated r and table r values using SPSS. Items are declared valid if calculated r > table r. Reliability testing used the Cronbach's Alpha method, with reliable criteria if the alpha value > 0.70, which indicates that the instrument is consistent and reliable. This study shows that the shift work system and workload have an effect on employee productivity at PT Setia Raya Mandiri. Partially, the shift work system has a positive effect with a significance value of 0.013, while the workload also shows a significant effect with a significance value of 0.00. Simultaneously, the two variables explain 72.5% of the variation in employee productivity.